Técnica Mézières para mejorar la postura corporal en adolescentes. - Muñoz Chango, Lilibeth Aurorita (2025)
Problems related to posture in adolescents are a topic of vital importance when talking about their quality of life. That is why postural correction techniques and treatments are presented as the main alternative to improve the quality of life of these adolescents. Therefore, in this work we have set the objective of analyzing the effectiveness of the use of the Mézières method in the re-education of posture in adolescents at the same time with a theoretical approach regarding a method based on the perception of different authors and with a selection of the articles necessary for the development of the bibliographic review. Within the study, a theoretical approach was carried out on previously prepared research on the Mézières method for postural correction. A qualitative and descriptive research approach was used. To select the articles necessary for the development of the study, the PEDro scale was used for the corresponding assessment. The main results indicated that the Mézières technique has a high level of effectiveness, compared to other physiotherapy methodologies. The advantage of the method is that it is easy to apply, focusing directly on the treatment of adolescents.